IMPLEMENTASI MANAJEMEN PEMBIAYAAN PENDIDIKAN BERBASIS SEKOLAH DALAM MENINGKATKAN MUTU PENDIDIKAN - Ahmad Yasir Amrirewa; Nailah Muazzarah Hafid; Sulkifli (PT. Sulthan Journal Publisher, 2026)
Education financing is a crucial aspect in ensuring the quality and sustainability of education delivery, particularly within the framework of School-Based Management (SBM), which grants schools autonomy in managing their resources. This study aims to analyze the concept, implementation, and role of school-based education financing management in improving the quality of education. The method used is a literature review library research with a qualitative descriptive approach, utilizing data sources such as scientific journals, books, and relevant regulations. The findings indicate that financial management conducted through the stages of planning, implementation, monitoring, and accountability carried out effectively, efficiently, transparently, and accountably can improve the quality of education, whether through the provision of facilities and infrastructure, the enhancement of teacher competencies, or the creation of a conducive learning environment. Thus, school-based education funding management plays a strategic role in improving the quality of education and producing high-quality graduates who are ready to face the demands of higher education and the workforce.